2008
DOI: 10.1038/nmeth.1199
|View full text |Cite|
|
Sign up to set email alerts
|

BAC TransgeneOmics: a high-throughput method for exploration of protein function in mammals

Abstract: The interpretation of genome sequences requires reliable and standardized methods to assess protein function at high throughput. Here we describe a fast and reliable pipeline to study protein function in mammalian cells based on protein tagging in bacterial artificial chromosomes (BACs). The large size of the BAC transgenes ensures the presence of most, if not all, regulatory elements and results in expression that closely matches that of the endogenous gene. We show that BAC transgenes can be rapidly and reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
650
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 577 publications
(666 citation statements)
references
References 40 publications
7
650
0
1
Order By: Relevance
“…HeLa‐Kyoto BAC lines stably expressing PRC1‐GFP 26 were courtesy of Ina Poser and Tony Hyman (MPI‐CBG, Dresden). Cells were grown in DMEM (1 g/l d ‐glucose, l ‐glutamine, pyruvate obtained from Sigma, St. Louis, MO, USA) with 50 μg/ml geneticin (Santa Cruz Biotechnology, Inc., Dallas, USA) and appropriate supplements.…”
Section: Methodsmentioning
confidence: 99%
“…HeLa‐Kyoto BAC lines stably expressing PRC1‐GFP 26 were courtesy of Ina Poser and Tony Hyman (MPI‐CBG, Dresden). Cells were grown in DMEM (1 g/l d ‐glucose, l ‐glutamine, pyruvate obtained from Sigma, St. Louis, MO, USA) with 50 μg/ml geneticin (Santa Cruz Biotechnology, Inc., Dallas, USA) and appropriate supplements.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a PBS score A was also obtained with six clones of the known interactor paracingulin (CGNL1) (8), whereas no PLEKHA7-interacting clones were detected with scores "B" (high confidence) or "C" (good confidence). For affinity purification of PLEKHA7 prior to mass spectrometry, a BAC clone harboring the mouse Plekha7 gene (RP23-350A9, BACPAC Resources Center) was recombined with an N-terminal GFP BAC tagging cassette (NFLAP: GFP_ PreScission_S-peptide_TEV_FLAG) (22). Precise incorporation of the tagging cassette was confirmed by PCR and sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…BAC clones RP11-413P14 and RP24-191F17 encoding human and mouse UNRIP genes respectively were obtained from BACPAC resource. They were tagged as previously described 32 and stable cell lines were selected on the basis of their neomycin (0.5 mg ml −1 , Invitrogen) or blasticidine (5 µg ml −1 , Invivogen) resistance.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate a potential association of UNRIP with SMN in HCT116 cells, we generated localization and affinity purification (LAP)-tagged UNRIP (UNRIP-LAP) cell lines using the TransgeneOmics approach 31,32 . Immunoprecipitation, followed by protein interaction analyses using mass spectrometry, revealed that human as well as mouse UNRIP-LAP efficiently co-purified the complete SMN complex (SMN1; SIP1, survival of motor neuron protein interacting protein 1, also known as GEMIN2; DDX20, DEAD (Asp-Glu-Ala-Asp) box polypeptide 20, also known as GEMIN3; and gem (nuclear organelle)-associated proteins 4-8, GEMIN4-8) and many of its substrates (Supplementary Table S3).…”
Section: Unrip Influences the Localization Of The Smn Complexmentioning
confidence: 99%
See 1 more Smart Citation